2017
DOI: 10.1007/s00248-017-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

Location, Root Proximity, and Glyphosate-Use History Modulate the Effects of Glyphosate on Fungal Community Networks of Wheat

Abstract: Glyphosate is the most-used herbicide worldwide and an essential tool for weed control in no-till cropping systems. However, concerns have been raised regarding the long-term effects of glyphosate on soil microbial communities. We examined the impact of repeated glyphosate application on bulk and rhizosphere soil fungal communities of wheat grown in four soils representative of the dryland wheat production region of Eastern Washington, USA. Further, using soils from paired fields, we contrasted the response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
2
17
1
Order By: Relevance
“…This fungus is described as a saprotrophsymbiotroph [26] capable of solubilizing phosphate in the rhizosphere [27]. Our results are consistent with other studies that identified Mortierella as a keystone taxa of the wheat rhizosphere unsensitive to cropping practices in Switzerland or the USA [9,28] with potential positive effects on wheat yield in Canada [29]. Altogether, these findings encourage future research to develop targeted cultivation approaches of the wheat-associated Mortierella fungi that seem to play a central role in the wheat microbiome across the world.…”
Section: Evidences For a Wheat Core Microbiome And Identification Of supporting
confidence: 91%
See 1 more Smart Citation
“…This fungus is described as a saprotrophsymbiotroph [26] capable of solubilizing phosphate in the rhizosphere [27]. Our results are consistent with other studies that identified Mortierella as a keystone taxa of the wheat rhizosphere unsensitive to cropping practices in Switzerland or the USA [9,28] with potential positive effects on wheat yield in Canada [29]. Altogether, these findings encourage future research to develop targeted cultivation approaches of the wheat-associated Mortierella fungi that seem to play a central role in the wheat microbiome across the world.…”
Section: Evidences For a Wheat Core Microbiome And Identification Of supporting
confidence: 91%
“…Chaetomium (Ascomycota, 60% of samples) described as pathotrophs or saprotrophs that also have been observed on wheat roots in different cropping systems and described as hub taxa [21,28,30].…”
Section: Evidences For a Wheat Core Microbiome And Identification Of mentioning
confidence: 99%
“…And while both barcoding and culture surveys detected other pathogens, none responded to glyphosate (Supplementary Data). Our results are consistent with previous metabarcoding studies [20, 21].…”
Section: Discussionsupporting
confidence: 94%
“…Greenhouse studies with GR wheat conducted in the Pacific Northwest found only minor effects of glyphosate on microbial communities, and determined site was a major driver of soil microbial community structure [20, 21]. While these studies did detect effects of glyphosate on the prevalence of a few microbial taxa, they applied glyphosate at twice the recommended rate, increasing the likelihood that the microbial community experienced a significant effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation